Optimalisasi Smart Public Management di Kantor Wali Nagari Pasie Laweh Lubuk Alung untuk Pembangunan Berkelanjutan - Candra Efendi, Erizal; Ningsih, Yulia (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The implementation of Smart Public Management (SPM) in village governance aims to enhance efficiency, transparency, and public participation in administrative services. This study analyzes the optimization strategy of SPM at the Pasie Laweh Lubuk Alung Village Head Office to support sustainable development. A qualitative descriptive approach was employed, using in-depth interviews, observations, documentation, and questionnaires with village officials and service users. The findings reveal several challenges in implementing SPM, including limited technological infrastructure, low digital literacy among officials, and limited community participation in tech-based services. To address these issues, strategies such as improving human resource capacity through digital training, strengthening infrastructure, and promoting the benefits of digital services to the public are necessary. Collaboration with educational institutions and the private sector is also essential to support the development of an optimal digital system. With the right strategies, the Pasie Laweh Lubuk Alung Village Head Office is expected to improve the effectiveness of digital public services, enhance governance transparency, and foster active community involvement. Optimizing Smart Public Management can serve as a model for other village governments in building a modern, efficient, and sustainable administrative system.